Teknologi 3D Printed Wall Bagi Rumah Sesebuah Mampu Milik - Samsudin, Siti Nurathirah Nabihah; Zainal, Rozlin; Mohd Noh, Hamidun; Kasim, Narimah (Research in Management of Technology and Business, 2023)
3D Printed Wall technology is a new technology that is increasingly being debated because it provides benefits in saving construction project time, especially in the housing sector. This technology is able to deal with the issue of affordable housing of a certain type due to the ever-increasing demand and need. The issue with the widespread use of 3D Printed Wall technology on construction sites is that the cost of expensive 3D printing equipment and materials makes the initial expense of using this technology very high, especially to provide more affordable housing stock. Therefore, the objective of this study is to identify the main challenges of implementing a 3D Printed Wall for an affordable home and identify the main strategy of implementing a 3D Printed Wall for an affordable home. This study involved 73 housing developers in Selangor using a quantitative approach through the distribution of questionnaires online and physical meetings. The percentage of respondents’ responses was 71.2%. Frequency and descriptive analysis were used to analyze the data for all objectives. The findings of the analysis for the first objective which is the main challenge of implementing 3D Printed Wall for an affordable house is transportation. While the second objective findings found that the main strategy for the implementation of 3D Printed Wall for an affordable house is worker safety. Therefore, this study can help developers by emphasizing the main challenge and main strategy in improving the implementation of 3D Printed Wall for an affordable house.